Theory of adhesive contact on multi-ferroic composite materials: Conical indenter. (15th December 2021) - Wu, F.; Li, C.
Abstract: There is still a challenge to realize controllable attachment and detachment in the adhesive devices. New approaches of the controllable or reversible adhesion need to be developed in a wider area. In order to study the influence of the electric and magnetic quantities on the reversible adhesion, the adhesive contact problem between a half-space of the multi-ferroic composite material and a rigid conical indenter is investigated. The classical Johnson–Kendall–Roberts (JKR) and Maugis–Dugdale (MD) models are extended to the framework of magneto-electro-elasticity. The corresponding physical fields are analytically obtained. With the help of the Griffith energy balance relations, the stable equilibrium states of the adhesive contact are established. The corresponding indentation forces and the penetration depths for the JKR and MD models are derived in the closed-form. It is found that the pull-out forces associated with the JKR model depend on the electric potential and magnetic potential in certain cases. The validity is discussed by comparing the obtained solutions with the experimental data in the context of the elasticity. Numerical results show that the adhesive contact behaviors may be adjusted and controlled by changing the electric potential, the magnetic potential and the half apex angle of the rigid conical indenter. The present analytical results not only are the theoretical fundament for the forthcoming indentation experiments at the micro/nanoscopic scale, surface force microscopy (SFM) and atomic force microscopy (AFM), but also serve as guiding bionic design of the robots and grippers with reverse adhesion. Highlights: Adhesive contact of a conical indenter is studied for multi-ferroic media. The physical fields for the JKR and MD model are analytically obtained. Based on the Griffith energy balance, the equilibrium relations are established. The contact behaviors including the pull-force are analyzed. Influence of adhesive effect on the physical quantities is numerically quantified.